Electrochemical surface oxide characteristics of metal nanoparticles (Mn, Cu and Al) and the relation to toxicity. (10th September 2016) - Hedberg, Y.S.; Pradhan, S.; Cappellini, F.; Karlsson, M.-E.; Blomberg, E.; Karlsson, H.L.; Odnevall Wallinder, I.; Hedberg, J.F.
Graphical abstract: Highlights: Surface oxide speciation on metal NPs possible to assess using an electrochemical tool. Electrochemical activity closely linked to metal release and cytotoxic response. Particle sedimentation is a source of error in intended NP dose in cell viability tests. Cell viability largely linked to surface oxide activity and corrosion Abstract: Most metal nanoparticles (NPs), except noble metal NPs, rapidly form a thin surface oxide in ambient conditions. The protective properties of these oxides improve or worsen depending on the environment, e.g., the human lung. Several properties, including the chemical/electrochemical stability and defect density, determine the capacity of these surface oxides to hinder the bulk metal from further oxidation (corrosion). The aim of this study was to investigate whether electrochemical surface oxide characterization of non-functionalized base metal NPs of different characteristics (Al, Mn and Cu) can assist in understanding their bioaccessibility (metal release) in cell media (DMEM + ) and their cytotoxic properties following exposure in lung epithelial (A549) cells. The composition and valence states of surface oxides of metal NPs and their electrochemical activity were investigated using an electrochemical technique based on a graphite paste electrode to perform cyclic voltammetry in buffer solutions and open circuit potential measurements in DMEM + . The electrochemical surface oxide characterization was complemented and verified by Raman spectroscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. The open circuit potential trends in DMEM + correlated well with metal release results in the same solution, and provided information on the kinetics of oxide dissolution in the case of Cu NPs. Extensive particle agglomeration in cell medium (DMEM + ) was observed by means of photon-cross correlation spectroscopy for all metal NPs, with sedimentation taking place very quickly. As a consequence, measurements of the real dose of added non-functionalized metal NPs to cell cultures for cytotoxicity testing from a sonicated stock solution were shown necessary. The cytotoxic response was found to be strongly correlated to changes in physico-chemical and electrochemical properties of the surface oxides of the metal NPs, the most potent being Cu NPs, followed by Mn NPs. No cytotoxicity was observed for Al NPs. The electrochemical surface oxide characterization corresponded well with other tools commonly used for nanotoxicological characterization and provided additional information.